2020
DOI: 10.3168/jds.2019-17224
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of pre- and postoperative plasma l-lactate measurements in calves with acute abdominal emergencies

Abstract: In both human and veterinary medicine, l-lactate is a well-established prognostic biomarker of disease severity and mortality and has also attracted increasing attention in bovine medicine due to the availability and validation of cheap and portable l-lactate analyzers. The aim of the present study was to evaluate the prognostic accuracy of plasma L-lactate measurements in calves with acute abdominal emergencies before and during the initial therapeutic period after surgical intervention. A prospective observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 45 publications
4
27
0
Order By: Relevance
“…In this context, recent studies (Lausch et al, 2019(Lausch et al, , 2020Giertzuch et al, 2020) have focused on the prognostic relevance of plasma l-lactate concentrations (l-LAC), because measurement of this metabolite can be easily performed using handheld l-lactate analyzers such as the Lactate-Pro device (Arkray; Buczinski et al, 2014). These studies revealed that markedly increased l-LAC is associated with an increased mortality risk, but that it is not possible to reliably predict the outcome of affected calves based on a single, preoperative measurement (Lausch et al, 2019(Lausch et al, , 2020. However, a remarkable finding was that survival rates of affected neonatal calves are low and the predictive accuracy of l-LAC can be improved when the age of the calf is additionally considered (Lausch et al, 2019).…”
Section: Jdsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, recent studies (Lausch et al, 2019(Lausch et al, , 2020Giertzuch et al, 2020) have focused on the prognostic relevance of plasma l-lactate concentrations (l-LAC), because measurement of this metabolite can be easily performed using handheld l-lactate analyzers such as the Lactate-Pro device (Arkray; Buczinski et al, 2014). These studies revealed that markedly increased l-LAC is associated with an increased mortality risk, but that it is not possible to reliably predict the outcome of affected calves based on a single, preoperative measurement (Lausch et al, 2019(Lausch et al, , 2020. However, a remarkable finding was that survival rates of affected neonatal calves are low and the predictive accuracy of l-LAC can be improved when the age of the calf is additionally considered (Lausch et al, 2019).…”
Section: Jdsmentioning
confidence: 99%
“…A cute abdominal emergencies in calves frequently require surgical intervention and high therapeutic expenditures. These conditions are associated with a grave prognosis, however, as indicated by reported success rates of 24 to 51% (Iselin et al, 1997;Mulon and Desrochers, 2005;Lausch et al, 2020). This issue has been attributed to irreversible organ damage due to rapid disease progression, concomitant complications such as sepsis and endotoxemia, as well as a high prevalence of peritonitis and malformations if neonatal calves are affected (Iselin et al, 1997;Mulon and Desrochers, 2005;Lausch et al, 2019).…”
Section: Jdsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Hyperlactatemia was diagnosed commonly in sick goats, especially diarrheic goats and those with haemonchosis. Several studies in humans, 38,39 cattle, 12,[40][41][42] horses, 6,43 and dogs 44 have reported hyperlactatemia to be present in the majority of critically ill patients.…”
Section: Factors Associated With Mortality In Hospitalized Sick Goatsmentioning
confidence: 99%